Penguatan Keterampilan Membaca dan Menulis Berbasis Nilai-Nilai Moderasi Beragama di Sekolah - Dina Putri Astuti; Ikke Wulan Dari; Naintyn Novitasari (Yayasan Darussalam Bengkulu, 2025)
This community service activity aims to provide information related to reading and writing skills by integrating the values of religious moderation in schools. The method used is service learning (SL), with four stages of service: (1) investigation; (2) preparation; (3) action; and (4) reflection. The results of this community service activity are that teachers and students gain a clear understanding of critical reading skills and interpret texts containing messages of tolerance, morality, and social values, while demonstrating a moderate attitude. The conclusion of this community service activity is that it has had a significant positive impact on improving students' literacy skills and fostering moderate and tolerant character